Réponses

2014-02-13T18:53:05+01:00
Meilleure réponse !
2014-02-13T18:55:16+01:00
(3x+1)² -(2x-5)²=0
on utilise a²-b²=(a+b)(a-b)
(3x+1)² -(2x-5)²= (3x+1+2x-5)(3x+1-2x+5)=(5x-4)(x+6)
donc x=4/5 ou x=-6
b)
(4x-1)² + 8x-5=0
16x²+1-8x+8x-5=0
16x²-4=0
(4x)²-2²=0
(4x+2)(4x-2)=0
x=1/2 ou x=-1/2
c)

(x-3)² - ( x+4)² (je te laisse faire celui-là)
d)
(x-1)² +2x=5
x²+1-2x+2x-5=0
x²-4=0
je te laisse finir


Non c'est faux:
ha bon
(2x-3-(x+4))=2x-3-x-4
donc ça fais 2x-3+4x ?
(2x+3)+(x+4) (2x+3)-(x+4)
(2x+3+x+4)(2x+3-x-4)
(3x+7)(x-1) ? NON